Methylation of Wnt Antagonist Genes and Wnt5a as Prognostic Markers in Colorectal Cancer - Rawson, James B.
DKK1, SFRP1, WIF-1, and Wnt5a encode Wnt pathway genes that are frequently silenced by promoter hypermethylation in colorectal cancer. Despite attractive biological consequences of these events, it is unclear whether they contribute to patient prognostication or may influence tumour cell biology within distinct patient subsets. I sought to determine the prognostic roles of these methylation events in a large cohort of colorectal carcinomas from Ontario and Newfoundland. Methylation was quantified and associated with patient clinicopathlogical features. Methylation was present in cancer tissue. DKK1, Wnt5a, and SFRP1 were strongly and independently associated with tumour subtype in a manner that suggested subtype-specific activity of Wnt signaling. Methylation of DKK1 was a borderline prognosticator of favourable outcome. These results offer intriguing insight into subtype-specific biology and lead to a proposed model whereby methylation-induced Wnt bias may contribute to patient outcome. MAST